2018
DOI: 10.1093/ee/nvy021
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Population Dynamics of Thrips Vectors of Soybean vein necrosis virus

Abstract: Thrips-infesting soybeans were considered of minor economic importance, but recent evidence of their ability to transmit a newly identified soybean virus, Soybean vein necrosis virus (SVNV), has raised their profile as pests. Season-long surveys were conducted using suction traps to determine the effects of temperature and precipitation on the spatiotemporal patterns of three vector species of SVNV, Neohydatothrips variabilis (Beach) (Thysanoptera: Thripidae) (soybean thrips), Frankliniella tritici (Fitch) (Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Thrips populations may have declined due to approaching winter temperatures and crop maturity, as thrips feed on the younger and more succulent parts of plants. Our results were similar to Bloomingdale et al [22] and Keough [14], who reported that the soybean thrips were positively correlated with degree days. We did not find any overwintering soybean thrips during soil sampling to accept Bloomingdale et al's [22] assumption that the soybean thrips in the north do not migrate south in the winter and instead overwinter in the north on perennials.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thrips populations may have declined due to approaching winter temperatures and crop maturity, as thrips feed on the younger and more succulent parts of plants. Our results were similar to Bloomingdale et al [22] and Keough [14], who reported that the soybean thrips were positively correlated with degree days. We did not find any overwintering soybean thrips during soil sampling to accept Bloomingdale et al's [22] assumption that the soybean thrips in the north do not migrate south in the winter and instead overwinter in the north on perennials.…”
Section: Discussionsupporting
confidence: 92%
“…Chitturi et al [29] monitored soybean thrips (N. variabilis) populations using sticky traps in Alabama, and found that the population of soybean thrips peaked in the third week of June in different counties (Tallassee, Auburn and Headland) in 2015, while in 2016 the maximum population of thrips were observed in first week of July in Tallassee, Auburn and Headland. In Indiana, Keough [14] observed higher N. variabilis numbers in the month of August on soybean crops. A study was conducted to determine effect of soybean vein necrosis virus and thrips infestation on yield reduction in soybeans planted under greenhouse conditions [30].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…variabilis , Frankliniella tritici , F. fusca , Frankliniella sp., Thrips tabaci , Phlaeothrips sp., Anaphothrips sp., and Echinothrips sp., Together, N . variabilis , F. tritici , and F. fusca account for nearly 75% of the thrips fauna found on soybean (Keough et al, 2018). Analysis of vector competence in the three thrips species revealed that tobacco thrips ( F. fusca ) and eastern flower thrips ( F. tritici ) are able to transmit SVNV albeit at a lower efficiency (36 and 6%, respectively) compared to the primary vector, soybean thrips (72%) (Keough et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Other insects have been collected routinely in the traps. Suction traps in Indiana in 2013 and 2014 were used to determine the effects of temperature and precipitation on the spatio-temporal patterns of three species of thrips (Thysanoptera: Thripidae) known to be vectors of soybean vein necrosis virus (SVNV): soybean thrips, Neohydatothrips variabilis (Beach); eastern flower thrips, Frankliniella tritici (Fitch); and tobacco thrips, Frankliniella fusca (Hinds) (Keough et al 2018). SVNV detections in mid-to-late August coincided with the peak catch of N. variabilis.…”
Section: Research Successes Using the Suction Trap Networkmentioning
confidence: 99%